Palm oil mill effluent (POME) treatment and conversion using non-catalytic hydrothermal method / Mohd Zahid Marzuki - Marzuki, Mohd Zahid (2022)
Palm oil mill effluent (POME) is considered as a major environmental pollution source due to its harmful characteristics and large volume of over 60 million tonnes generated annually. It is characterized by high oils and fats, chemical oxygen demand (COD) and biochemical oxygen demand (BOD) concentrations and therefore subjected to strict discharge parameter standard promulgated under Environmental Quality Act (EQA) 1974. The biochemical oxygen demand (BOD) and chemical oxygen demand (COD) of POME are typically in excess of 30,000 ppm and 50,000 ppm respectively. As such, POME is toxic to environment that requires proper management prior to final discharge to inland water bodies.